Use of TLS technology in highway construction - Plesník, Jiří; Staňková, Hana; Černota, Pavel (Geodesy and Cartography, 2023)
This article deals with issues related to the measurement of TLS technology, or 3D scanning in road construction. Based on the data and results obtained, a technological procedure for the use of TLS technology on highways and A-roads will be drawn up, mainly for monitoring the transition areas of bridges, which currently does not exist in the Czech Republic. A smooth connection between two different structures in the transition areas should provide a comfortable crossing of the bridge structure. In order to unambiguously determine the movements in these areas, it is necessary to eliminate any inaccuracies that may affect the final result. For this reason, it was necessary to use a combination of traditional geodetic methods and special geodesy methods. In addition, several innovative methods were used, which emerged in this work based on newly emerging facts. All these operations and the presentation of the results will be described in this work.